Focus on post-exertional malaise when approaching ME/CFS in specialist healthcare improves satisfaction and reduces deterioration - Wormgoor, Marjon E. A.; Rodenburg, Sanne C. (Frontiers in Neurology, 2023)
Background Post-exertional malaise (PEM) is considered a hallmark characteristic of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). This may also apply to subgroups of patients with long COVID-induced ME/CFS. However, it is uncertain to what extent PEM is acknowledged in routine specialist healthcare for ME/CFS patients, and how this affects patient outcomes. Objective This study aims to evaluate to what extent ME/CFS patients experienced focus on PEM in specialist healthcare practice and its significance for outcome and care quality. Methods Data from two online cross-sectional surveys covering specialist healthcare services for ME/CFS patients at rehabilitation institutes in Norway and two regional hospitals, respectively, were analyzed. Evaluations of 788 rehabilitation stays, 86 hospital consultations, and 89 hospital interventions were included. Logistic regression models and Mann–Whitney U-tests were used to quantify the impact of addressing PEM on health and functioning, care satisfaction, or benefit. Spearman’s rank correlation and Cronbach’s alpha of focus on PEM with the respondents’ perception of healthcare providers’ knowledge, symptom acknowledgment, and suitability of intervention were assessed as measures for care quality and their internal consistency, respectively. Results PEM was addressed in 48% of the rehabilitation stays, 43% of the consultations, and 65% of the hospital interventions. Failure to address PEM roughly doubled the risk of health deterioration, following rehabilitation (OR = 0.39, 95% CI 0.29–0.52; 40.1% vs. 63.2% P = <0.001) and hospital intervention (OR = 0.34, 95% CI 0.13–0.89; 22.4% vs. 45.2%, p = 0.026). The focus on PEM (PEM-focus) during the clinical contact was associated with significantly higher scores on patients’ rated care satisfaction and benefit of both consultation and intervention. Furthermore, addressing PEM was (inter)related to positive views about healthcare providers’ level of knowledge of ME/CFS, their acknowledgment of symptoms, obtained knowledge, and the perceived suitability of intervention (Cronbach’s alpha ≥0.80). Discussion PEM is still frequently not acknowledged in specialist healthcare practice for ME/CFS patients in Norway. Not addressing PEM substantially increased the probability of a decline in health and functioning following the intervention and was strongly associated with reduced perceived care quality, satisfaction, and benefit. These findings may be related to the applied explanatory models for ME/CFS and are most likely of relevance to long COVID.